ANALISIS GAYA KEPEMIMPINAN IDEAL UNTUK GENERASI MILENIAL - Danang Nugroho; Dewi Nur Utarie; Dinda Sukmawati; Indri Dinaprilla; M. Wildan Firmansyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Leadership plays a crucial role in managing an organization and is essential in various types of organizational structures. A leader is tasked with planning and managing available resources while influencing and guiding team members to achieve their best performance. Successful leadership depends on the leadership style employed and the satisfaction level of team members. Being an effective leader in the millennial era and beyond is a significant challenge. Over time, many leaders emerge in response to the demands and environmental conditions of their time. In the millennial generation, the success of governance will be achieved when leaders meet the qualifications as credible individuals, possessing skills, intelligence, and a forward-looking vision. However, effective leadership also requires integrity, honesty, and loyalty to the interests of society. Leadership in the millennial era should promote independence and entrepreneurial spirit among millennials. Building a nation requires a strong foundation in the form of independence and entrepreneurial spirit.